(untitled) (Multidisciplinary Journal of Science and Technology, 2024)
This article delves into the intricate connections between cognitive psychology and simultaneous interpreting, exploring the cognitive processes, mechanisms, and challenges encountered by interpreters. It examines how cognitive psychology principles influence and shape the performance of simultaneous interpreters, shedding light on the complexities and cognitive demands inherent in this form of language mediation.